Desain Web E-Commerce Berbasis Blogspot sebagai Media Promosi Butik Berkah Hijab Kendal - Muhammad Sholikhan; Yayuk Kurniawati (Pixel :Jurnal Ilmiah Komputer Grafis, 2021)
In this digital era, business competition is increasingly competitive. A business is required to conduct continuous evaluation. In today's business world, e-commerce is a necessity to increase business competition and product sales. In the use of e-commerce, buying and selling and marketing activities will be easier and more efficient where consumers will find it easier to buy and sell the desired goods without having to leave the house so as to show the ease of transactions, reduce costs and speed up the transaction process. This study aims to create a Blogspot-Based E-Commerce Web Design as a Promotional Media for Kendal Hijab Blessing Boutique. It is hoped that the design and development of an e-commerce blog can help business actors to market their products more broadly so that they can increase sales and make it easier for consumers to transact, especially at the Kendal Hijab Berkah Boutique.